Postnatal weight gain in infants of HIV infected mothers: is formula feeding truly advantageous?. (24th May 2012) - Mackenzie, K; Wright, CM; Mactier, H
Abstract : Aims: British HIV Association guidelines recommend formula feeding for infants born in the UK to HIV infected mothers. Formula feeding is however associated with childhood obesity and adverse implications for longer term health. Local clinical observation suggested that infants of Black African HIV infected mothers demonstrate accelerated postnatal growth compared to their Caucasian counterparts, perhaps due to lack of familiarity with formula feeding in the former population. The aim of this study was to review postnatal growth in an unselected population of HIV exposed infants, and to compare different ethnic groups. Methods: Retrospective case note review of all HIV exposed infants born at term over a three year period in a single centre (n= 44). 36 infants were born to Black African mothers, and 8 infants to Caucasian mothers. The majority of mothers (91%) had an undetectable viral load at delivery. Infants were weighed and measured at outpatient follow up at six weeks, three months, nine months and 18 months of age. Weight-for-age, length-for-age and BMI-for-age Z scores were calculated using LMS Growth software. Results: Birth weights did not differ between groups. As a whole infants born to HIV infected mothers grew similarly to WHO standards until nine months of age, but Black African infants were heavier than Caucasian infants by age three months (mean (SD) BMI z-score 0.55 (1.06) v −0.34 (0.93); p<0.05). Both groups showed accelerated weight gain to 18 months: mean (SD) BMI z-score 1.58 (0.78) in Black African v 0.94 (1.04) in Caucasian infants. Conclusion: Infants born in Scotland to Black African HIV infected mothers are on average above the 91st WHO centile for BMI by 18 months of age. Further research is required to establish if this reflects inappropriate formula feeding practice. Babies of HIV infected mothers with undetectable viral load at delivery are at very low risk of perinatal transmission: feeding recommendations should consider the potential longer term adverse consequences of formula feeding in this population.